Stepping up to the plate: Planning for a lasting health legacy from major sporting events - Thompson, D.; McAteer, S.; Davies, N.; Hoffman, A. (World Innovation Summit for Health, 2020)
Major sporting events bring millions of people together from across the globe, providing many benefits to host countries, including valuable infrastructure investment, increased tourism income and a heightened sense of national pride. However, such events also present a multitude of challenges and risks. Legacy planning is often not prioritized when dealing with the many stressful demands of delivering a successful event and can result in a missed opportunity in realizing future health and public health benefits. This report demonstrates how effective planning for these challenges can be leveraged to achieve three primary health goals: • Protect health during the event: Protect the health of visitors, spectators, participants and the local population during the event. • Establish a health and public health legacy: Plan for the sporting event to deliver assets, change health behaviors, encourage infrastructure investment and develop capacity. • Share learning: Codify and disseminate lessons learned to future hosts..